The larvae of West Palaearctic Eurylophella Tiensuu, 1935 (Ephemeroptera: Ephemerellidae), with description of a new species from Georgia - Martynov, Alexander V.; Palatov, Dmitry M.; Godunko, Roman J. (Zootaxa, 2015)
Eurylophella korneyevi sp. nov. (larva) is described from the Kintrishi River within the Caucasus region of Georgia, Autonomous Republic of Adzharia. In addition to morphological data, biological and distribution data are also presented. The new species can be differentiated from other Eurylophella species by the shape of submedian tubercles on abdominal tergites, the structure of the dorsal subdivisions of the lower lamella of gills IV, and the shape and relative development of occipital tubercles. Distinguishing features of E. korneyevi sp. nov., Eurylophella karelica Tiensuu, 1935 and Eurylophella iberica Keffermüller & Da Terra, 1978 are given. The possibility of using chaetotaxy in the taxonomy of the genus is analyzed in detail for the West Palaearctic species of Eurylophella.